A near-range plant invasion homogenizes riparian vegetation but leads to more productive bird communities. Issue 3 (24th June 2021) - Stinson, Lani T; Pejchar, Liba
Abstract: Biological invasions are a leading driver of biodiversity loss and population declines worldwide. While much research has focused on understanding the effects of long-distance (e.g., cross-continental) invasion, the potential impacts of species that invade close to or within their native ranges are relatively understudied. We investigated the effects of the near-range introduction of a non-native plant, New Mexico locust ( Robinia neomexicana ), on riparian plant and bird communities in northwestern Colorado, USA. By surveying plant and bird communities and examining nest success and productivity in riparian forest with and without locust, we evaluated the following ecological responses to invasion: (1) tree and shrub richness and density; (2) bird species richness, occupancy, and abundance; and (3) avian reproductive success. Our results demonstrate biotic homogenization of the plant community with increasing intensity of locust invasion, yet we found little evidence for negative effects on avian habitat use or reproductive success. Instead, locust invasion showed a positive effect on nest productivity, with significantly higher brood sizes and numbers of young fledged for nests in invaded habitats compared to those where locust was absent. Because climate change is already leading to shifts in species distribution patterns, we suggest that understanding the ecological consequences of plant invasions that occur within or near historic ranges will advance the science and practice of invasive species biology in a changing world. Our findings of mostly neutral to positive effects of locust suggest that near-range plant invasions may not always negatively impact community structure. Lay Summary: Near-range introductions occur when species are brought to areas close to their native ranges. Though much less studied than traditional long-distance invasions, they have the potential to transform native plant and animal communities. New Mexico locust, a fast-growing woody plant, was introduced to a valley in Colorado, USA, near its northern range boundary. We collected data on plants and birds in areas with and without locust and found that locust decreased the diversity of plant species but had neutral to positive impacts on the bird community. Nests located in areas with locust produced more nestlings than those in uninvaded sites, suggesting locust may provide benefits for some songbirds, potentially in the form of enhanced nest protection and/or food availability. Near-range introductions are likely to become more common with climate change; our results suggest these introductions may have mixed effects on plant and animal communities. Graphical Abstract: